FORMULATION AND EVALUATION OF SOILD LIPID NANOPARTICLES OF SERTRALINE HYDROCHLORIDE (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
Depression is a global affective and common mental disorder, with over 264 million people experiencing it. It is characterized by depressed mood, loss of interest, feelings of guilt or low self-worth, disturbed sleep or appetite, and poor concentration. A new class of colloidal delivery system has been introduced that encompasses a number of advantages over the conventional dosage forms and one of it includes the solid lipid nanoparticles (SLN) with the major advantage of been controlled and site-specific drug delivery. It is made up of a solid core and phospholipid shell having high drug loading to enhance bioavailability. Sertraline hydrochloride is an antidepressant drug used for brain targeting. The main objective of the work was to formulate Sertraline hydrochloride-loaded solid lipid nanoparticles and to screen the effect of formulation with process variables on the performance of these formulated solid lipid nanoparticles. Hot homogenization technique was used to formulate the solid lipid nanoparticles using of 32 factorial designs. The effect of independent variables on the concentration of Poloxamer 188 and Glyceryl monosterate on viscosity and drug release was studied. SLNs containing sertraline hydrochloride were prepared and evaluated. The results depicted F6 as an optimized formulation with an entrapment efficiency of 87.36 ± 1.45% and a drug release of 84.26 ± 1.10%. With the thorough screening study, the enrichment of Sertraline hydrochloride entrapment was attained with good particle size and controlled release. The factorial design confirmed its influence and significance in determining and understanding both formulation and process variables affecting the quality of SLNs.